Analisis Frekuensi Pribadi Dan Modus Getar Struktur Pesawat Tanpa Awak Tipe Flying Wings - Lovely Son; Rachmad Afandi (METAL: Jurnal Sistem Mekanik dan Termal, 2018)
One of the important consideration in designing an unmanned aerial vehicle (UAV) is the dynamics characteristic of UAV structure. The dynamics characteristic of UAV structure can be evaluated from its dynamic parameters such as : natural frequencies and mode shape. These parameters play an important role in determining the system’s dynamic response. In general, a low stiffness structure is more sensitive to the dynamic load in comparison with a high stiffness structure. In this research, modification UAV structural stiffness is conducted by varying rib and spar number and configuration on UAV wing.  Evaluation of rib and spar number and configuration effect to the natural frequency and mode shape of UAV structure is conducted numerically and experimentally. The simulation results show that the natural frequencies increases with increasing of the number of spar and decreases with decreasing of the number of rib.